DIGITAL TRANSFORMATION AS A CHANCE FOR SMALL BUSINESS DEVELOPMENT (International Journal of Management Trends: Key Concepts and Research, 2022)
Human civilization has entered a completely new era in which the digital, virtual, innovative and imaginary becomes the main driver of national and economic development. Digital transformation has become the “conditio sine qua non” of modern organizations. The issue of digital transformation of business has become the subject of interest of theoreticians and practitioners, but only in the last few years. That is why its ultimate goal is to create added business value. The use and introduction of a large number of digital technologies in a small business by itself will not provide the expected benefits in the process of innovation itself. The highlighted importance of digital transformation refers to user experience, operational processes, business models, employee experience and digital platforms, as well as to the key domains of small business operations that digitalization is changing. The task of the work indicates the impact that digital transformation in the business process has on a small entrepreneurial venture. Bearing this in mind, the goal itself is focused on the possible directions of digital transformation of business in conditions of strong penetration of digital technologies and strong impact on small business.